25 Years of Progressive in Numerical Modeling for Ground Control ? What Have We Accomplished and Where Do We Go Next? - Keith A. Heasley (International Conference on Ground Control in Mining, 2006)
Exactly 25 years ago this month (August 12, 1981), IBM introduced the ?Personnel Computer? with a 16 bit operating system called MS-DOS 1.0. Since then, Moore?s Law, which essentially states that computer capability will doubled every 18 months, has been fully evident in the computer industry. As computers have advanced from main frames to initial personnel computers to the powerful graphical workstations of today, numerical modeling for ground control in mining has followed closely behind. Twenty five years ago, many numerical methods for solving ground control problems were little more than equations on a piece of paper. In the intervening years, these numerical models have grown from initial trial programs to highly-complex computational systems with numerous capabilities for different material behavior, failure criteria, gridding methods, discontinuities, etc. In some instances, the capability of the programs has quickly outstripped the geo-technical modeler?s ability to get accurate, realistic input and boundary conditions. This paper will look at: how numerical models have evolved in the last 25 years, how the models have been applied to ground control problems in that time period, and where numerical modeling is headed in the immediate future.